A multi-criteria spatial approach for determination of the logistics center locations in metropolitan areas. (September 2022) - Önden, İsmail and Eldemir, Fahrettin
Abstract: Logistics centers are providing integrated services. Due to they are the central points of the logistics activities, these facilities have considerable influence over logistic structure of the cities. Therefore, using spatial data is a way to use the power of the data science instead of considering limited parameters in determining their location. For a location decision, it is necessary to evaluate different decision parameters, especially spatial suitability. A methodology that combines a complex problem structure, expert opinion, geographical characteristics and mathematical modeling approach that provides cost minimization is proposed in the study for multiple logistic facility location analyzes. The proposed method combines different analysis methods under a systematic approach including economic analysis of the centralization level. Results showed that the proposed methodology is capable of dealing such problems with the given considerations. Graphical abstract: Unlabelled Image